Acceptance of televideo technology by adults aging with a mobility impairment for health and wellness interventions. (February 2017) - Mitzner, Tracy L; Stuck, Rachel; Hartley, Jordan Q; Beer, Jenay M; Rogers, Wendy A
Televideo technology (e.g., Skype) has potential to support adults as they age by facilitating their interactions with people remotely; this potential may be even greater for adults aging with pre-existing mobility impairments, who face challenges interacting with others in person due to lack of transportation or accessibility. Our research employed questionnaire and interview methodologies to investigate this understudied population about their attitudes toward televideo technology for supporting social engagement, healthcare provider access, and physical activity. Participants were 14 adults aging with self-reported mobility impairments (50–70 years of age). Overall, participants were open to accepting televideo technology for social engagement, healthcare provider access, and physical activity. Participants perceived these technologies to be useful and perceived additional benefits, including the feeling of "being there" by enabling the viewing of facial expressions and the environment of the other person. Concerns included perceptions that televideo technologies lack security and privacy. Participants also expressed concerns that these technologies are difficult to use and are difficult to learn to use. The findings have implications for education, training, and deployment of televideo technology for home-based interventions for adults aging with pre-existing mobility impairments.